Pengaruh Beban Kerja dan Stres Kerja melalui Variabel Mediasi Kepuasan Kerja terhadap Kinerja Karyawan PNM Mekaar Area Batang 2 - Ika Suci Wulandari; Sutrisno; Bayu Kurniawan (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2022)
This study aims to examine and analyze the effect of workload and work stress through the mediating variable of job satisfaction on the performance of PNM Mekaar Area Batang 2 employees. Respondents in the study were all employees of PNM Mekaar Area Batang 2 involving 100 employees. The data analysis technique used is PLS-SEM (Partial Least Square-Structural Equation Model). The data processing of this research uses the SmartPLS 3.0 tool. This study shows that workload has an effect on employee job satisfaction with a P-Value value of (0.029) and a Path Coefficient value of (0.296). Job stress has an effect on employee job satisfaction with a P-Value value of (0.010) and a Path Coefficient value of (0.358). Job satisfaction has an effect on employee performance with a P-Value value of (0.001) and a Path Coefficient value of (0.334). The workload has no effect on employee performance with a P-Value value of (0.361) and a Path Coefficient value of (0.150). Job stress has no effect on employee performance with a P-Value value of (0.103) and a Path Coefficient value of (0.290). Workload has no effect on employee performance which is mediated by job satisfaction with a P-Value value of (0.082) and a Path Coefficient value of (0.099). And work stress has an effect on employee performance which is mediated by job satisfaction with a P-Value value of (0.047) and a Path Coefficient value of (0.120).